Peran Rezim Internasional International Civil Aviation Organization (ICAO) dalam Penanganan Kasus Penembakan Pesawat Sipil Ukraina oleh Militer Iran Januari 2020 - Ardianti Mawardika; Mohamad Rosyidin; Muhammad Faizal Alfian (Journal of International Relations, 2022)
The development of the aviation world is growing rapidly and often involves crossing national borders, so international civil aviation security standards are needed to remain safe and under control. Chicago Convention 1944 became the pioneer to the formation of the International Civil Aviation Organization which is an Organization of International Civil Aviation with a standard rules and practices under the Chicago Convention. As an international civil aviation organization, ICAO has binding rules for its member countries to then be implemented in domestic regulations. January 2020 Iranian military fired missiles at PS752 which is an international civilian aircraft of Ukraine. As an ICAO member country, Iran should have reported to ICAO for the shootings that had occurred. By using the International Regime Effectiveness Theory according to Underdal, this paper aims to determine the role of the ICAO Regime in Handling the PS752 Shooting. The result of this research is an analysis of the effectiveness level of ICAO as the International Regime of International Civil Aviation.